2014
DOI: 10.1002/ajpa.22590
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects in the primate community of the biological dynamics of forest fragments project,Amazonas,Brazil

Abstract: While much is known about abiotic and vegetative edge effects in tropical forests, considerably less is known about the impact of forest edges on large mammals. In this study, we examine edge effects in a primate community to determine: 1) the distance from the edge over which edge effects in primate density are detectable, 2) whether individual species exhibit edge effects in their density, and 3) whether biological characteristics can be used to predict primate presence in edge habitats. Given their importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 89 publications
(93 reference statements)
5
34
0
3
Order By: Relevance
“…1A, 2C, and 3A). For forest birds, edge effects along hard edges are generally thought to be negative (sensu Gates & Gysel 1978, but see Zurita et al 2012, Lenz et al 2014, and the BDFFP is no exception (Laurance et al 2002). However, due to land abandonment at the BDFFP, edges have become softer over time, and now appear to provide resources for these three rain forest species-two of which, X. pardalotus and F. colma, are typically defined as forest interior rather than edge species (Cohn-Haft et al 1997, Krabbe & Schulenberg 2003, Marantz et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…1A, 2C, and 3A). For forest birds, edge effects along hard edges are generally thought to be negative (sensu Gates & Gysel 1978, but see Zurita et al 2012, Lenz et al 2014, and the BDFFP is no exception (Laurance et al 2002). However, due to land abandonment at the BDFFP, edges have become softer over time, and now appear to provide resources for these three rain forest species-two of which, X. pardalotus and F. colma, are typically defined as forest interior rather than edge species (Cohn-Haft et al 1997, Krabbe & Schulenberg 2003, Marantz et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that mantled howler monkeys, as large folivore–frugivores with preference for high canopy (Arroyo‐RodrĂ­guez & Dias, ; Fleagle & Mittermeier, ), would show positive riparian edge effects, with higher encounter rates at riparian forest edge compared to interior. Research on other howler species revealed positive edge effects (Lenz et al, ), suggesting mantled howlers may exhibit the same tendencies. As folivore–frugivores (di Fiore et al, ; Glander, ), their relatively flexible dietary strategy allows them to persist in relatively low‐quality forest patches (Estrada, ).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to natural edges, anthropogenic edges are created by human‐caused fragmentation of otherwise continuous landscapes. Sharp forest edges, such as borders between protected rain forest and developed land, are increasingly present worldwide, particularly in tropical environments (Lenz, Jack, & Spironello, ; Stevens & Husband, ). Both natural and anthropogenic forest edges are usually poor habitats for biota adapted to forest interior; tree mortality increases and there are greater canopy gaps (Laurance et al, ), and both plant and animal biomass typically decreases near edges or transition zones (Arroyo‐RodrĂ­guez & Mandujano, ; Estrada, Anzures, & Coates‐Estrada, ; but see Laurance et al, ; Lopez de Casenave et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in dry forests, where rainfall is scarce for months at a time, capuchins appear to be constrained by access to reliable above‐ground water sources (Fedigan & Jack, 2001). Howler monkeys, in contrast, are perhaps less reliant on above‐ground water sources (Glander, 1978) and more capable of tolerating fragmented habitats due to their leaf‐based diet (Williams‐GuillĂ©n et al, 2013; i.e., showing neutral or positive edge effects: Bolt et al, 2018 ( A. palliata ); Lenz, Jack, & Spironello, 2014 ( A. macconelli ); surviving in fragmented habitats: Asensio, Arroyo‐RodrĂ­guez, Dunn, & CristĂłbal‐Azkarate, 2009 ( A. palliata mexicana ); Boyle & Smith, 2010 ( A. macconelli )). Nevertheless, when forest fragmentation is accompanied by other factors (e.g., fewer large trees, increased hunting pressure, etc.)…”
Section: Introductionmentioning
confidence: 99%